The rights of African landlocked States under the United Nations Convention on the law of the sea: real or illusory rights? - Mubima, Nancy Napol (Department of Public Law, 2022)
The United Nations Convention on the Law of the Sea (LOSC) 1982 has been acclaimed as a constitution for the seas and a solution to several contentious issues that previous conferences on the law of the sea had been unable to settle. During the nine years of negotiation of the LOSC, the case of landlocked States was discussed extensively and, in an attempt to redress landlocked States' natural disadvantages, several rights were ultimately granted to this group of States by the Convention. The dissertation firstly identifies the rights conferred by the Convention on landlocked States in general and analyses the nature of these rights and their relevant provisions in the Convention. Thereafter, with a special focus on African landlocked countries, the dissertation seeks to determine the extent to which these particular States have been able to exercise the rights to access the sea, to participate in the exploitation of the living resources of their neighbouring coastal States' EEZs and to share in the revenue derived from exploitation activities in the Area. The dissertation attempts to determine whether African landlocked States have been able to exercise these rights and enjoy the resulting benefits or whether they have failed to do so and, as a result, perceive these rights to be illusory. With the help of case studies, the obstacles and factors that influence the exercise of each of these rights are examined. A study of the various initiatives put forth by the African Union (AU) and other regional and international bodies to enable the African landlocked States better exercise these rights, and if possible, make them a reality concludes the dissertation.